2012
DOI: 10.5539/ijef.v4n6p51
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Accruals Quality, Earnings Persistence and Accruals Anomaly in the Canadian Context

Abstract: The aim of this paper is twofold. First, we examine whether accruals' low reliability explains bias in earnings persistence coefficient. Second, we test whether investors overestimate persistence of low reliability components of accruals. To test our hypotheses, we use a sample of Canadian firms listed on the Toronto Stock Exchange for the period 2002-2005. The results show that: (1) low reliability of some accruals components seems to partially explain bias in earnings persistence coefficient; (2) not only do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, there are some limitations in this study, First of all, our sample includes 20 firm-observations from the financial industry, while most of the prior studies exclude such firms (with a four-digit Standard Industrial Classification (SIC) between 6000 and 6999) because it is difficult to calculate the discretionary accruals for this category of firms (van Tendeloo & Vanstraelen, 2005;van der Poel & Vanstraelen, 2011;Boubakri, 2012). However, only 20 of our 3049 firm-observations are from the financial industry.…”
Section: Conclusion Limitations and Recommendationsmentioning
confidence: 99%
“…However, there are some limitations in this study, First of all, our sample includes 20 firm-observations from the financial industry, while most of the prior studies exclude such firms (with a four-digit Standard Industrial Classification (SIC) between 6000 and 6999) because it is difficult to calculate the discretionary accruals for this category of firms (van Tendeloo & Vanstraelen, 2005;van der Poel & Vanstraelen, 2011;Boubakri, 2012). However, only 20 of our 3049 firm-observations are from the financial industry.…”
Section: Conclusion Limitations and Recommendationsmentioning
confidence: 99%
“…When investors evaluate the company's future in investment decisions, accounting information plays an important role in this assessment. Thus, considering the major role of capital in the economy of any country, it is necessary that investors be aware of the financial information of the companies to lead to good investment in the capital market and optimal allocation of resources on the capital market (Boubakri, 2012). For financial analysts to able to successfully predict future performance, there is a need for financial statements particularly accounting earnings.…”
Section: The Concept Of Value Relevancementioning
confidence: 99%
“…Furthermore, evidence from Sloan (1996); Richardson et al (2005); Dechow &Ge ( 2006) shows that accrual accounting contributes to the observed decline in earnings persistence such that accrual component of earnings is less persistence of earnings than the persistence of cash flows The studies by Sloan (1996); Richardson et al (2005); Oei, Ramsay & Mather, 2008;Boubakri, (2012); Chen &Shane (2014) further reveal that accrual leads to low persistence of earnings but does not lead to low persistence of cash flows component of earnings. It is reported that the ability of cash flows to predict future earnings is higher than accrual earnings.…”
Section: Literature Reviewmentioning
confidence: 99%